Audiobook-Mediated Learning: Investigating the Effects of ‘Storynory’ on Listening Skill - Erlynda Christia Purba; Dewi Yana; Aulia Putri; Warno Edi (Lectura : Jurnal Pendidikan, 2023)
Audiobooks have received attention as learning media, and have been studied for language-learning benefits. However, Storynory audiobooks’ effects on listening skills are poorly studied. Understanding its effect can help educators and policymakers create effective instructional approaches. So, the objective of this study was to assess the potential impact of ‘Storynory’ audiobooks on the listening abilities. This study was carried out at SMA Kartini Batam on the odd semester of 2022/2023 academic year, employing a quantitative with quasi-experimental design. This study used two tests in collecting the data, namely a pre-test and a post-test. The study’s control group was comprised of 27 students, whereas the experimental group was composed of 19 students. The process of analyzing the data entailed the use of the Shapiro-Wilk technique to examine normality, the Levene Statistics test to evaluate homogeneity, and the t-test formula for the purpose of hypothesis testing. Based on the hypothesis testing, it was found that the t-value was 5.006, which exceeded the critical t-value of 2.101 (5.006 > 2.101). Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The findings indicate a moderate and statistically significant impact of Storynory implementation on the auditory aptitude of tenth-grade students at SMA Kartini Batam. This study provides evidence-based for teachers to improve listening instruction using Storynory Audiobook. Since this study was only carried out on a limited population, it is recommended that further researchers expand the population to provide a broader understanding of its effectiveness and generalization.